Analisis Prinsip-Prinsip Pengelolaan Lingkungan Hidup yang Berkelanjutan Sebagai Dasar Penilaian Dokumen Evaluasi Lingkungan Hidup (DELH) - Azizah Mahirah Rizki; M. Abdus Salam Jawwad; Slamet Sujarwo (Yayasan Literasi Sains Indonesia, 2023)
Environmental Evaluation Document (DELH) is a document used to assess the impact of a project on the environment. In ensuring the sustainability of the principles of sustainable environmental management, it is an important component so that the principles of environmental management can be taken into consideration in preparation of the DELH and become considerations for the development of policies for sustainable environmental management. This study aims to analyze the Environmental Evaluation Document licensing submitted by various companies with the principles of sustainable environmental management. This study examines how these principles can be applied in DELH, identifies the application of these principles in improving the quality of DELH and how DELH can be used as material for consideration in developing policies for sustainable environmental management with qualitative and explorative methods. This results of this study are expected to contribute to the development of DELH as an effective evaluation tool and in accordance with the principles of sustainable environmental management.